Commentary: Cultural Issues in Decisionmaking - Muaygil, Ruaim (Cambridge quarterly of healthcare ethics, 2016)
This case presents several fundamental ethical issues. The first issue is the patient’s refusal of treatment (a nasogastric tube [NGT] insertion). Second, the patient’s refusal of a seemingly beneficial treatment, combined with her medical history, ultimately necessitates an assessment of her decisionmaking capacity. Third, the sister’s reluctance to participate in decisionmaking requires a discussion of appropriate surrogate decisionmakers. Finally, the main ethical component to this case is a cultural one, which should be addressed appropriately.